9+x=93

Simple and best practice solution for 9+x=93 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+x=93 equation:


Simplifying
9 + x = 93

Solving
9 + x = 93

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + x = 93 + -9

Combine like terms: 9 + -9 = 0
0 + x = 93 + -9
x = 93 + -9

Combine like terms: 93 + -9 = 84
x = 84

Simplifying
x = 84

See similar equations:

| 2.4=x+3.7 | | 4(d+6)= | | 890/2 | | -3x^3+10x^2-3x=0 | | 5(2c+3)-8=3(4c+2)-2c | | 0.5x-0.3(50+x)=0.3(50) | | 6+7x=4x+1 | | 27=x3/2 | | 5(4-6x)=8+6(7+2x) | | 4^2/2=3y | | 2(7b-4)=b-21 | | 5x+8+7x+10=90 | | 3(3+2x)=-45 | | 24k^2-31k-36=-k | | n(5n+4)=0 | | h=t*t+14t+0 | | x^2(8x-3)4(8x+3)=0 | | h(x)=x^4+2x^3-3x^4 | | 2x-17+3x+7=180 | | -2/3-4/3 | | (12-v)=-3 | | 4X+2Y=336 | | (2x-1)+(6x+2)+(5x+3)=180 | | -2/3-4/3=0 | | 3a+-b=6 | | 4x-2(-1)=4x-23(-5) | | y=3x+8-(12x) | | 81x^2=100x | | 15a^2-8=29a+6 | | 3264/5.10 | | 3x-2h=46 | | 6x+10+3x=118 |

Equations solver categories